Evaluation of clinical profile of acute pancreatitis in a tertiary centre - Goel, Kanwar Singh; Garg, Gulshan; Singla, Sham L. (International Surgery Journal, 2021)
Background: Acute pancreatitis is a disease for which patients are in large numbers, etiology, clinical presentation and examinations are varied. Disease may be mild or severe, may lead to multi organ failures and death. Most common cause is biliary tract diseases. Other causes are alcohol consumption, post ERCP, trauma, idiopathic and drugs, viral infections, genetic mutations and connective tissue disorders. Methods: This is a prospective observational study conducted at SGT medical college, Budhera, Gurugram, Haryana, from January 2017 to June 2019 in 100 consecutive patients. Data collection included detailed recording of demography of patient, clinical presentation, any history of biliary tract disease, alcohol consumption, trauma, ERCP, comorbidities. Data was also collected about investigations done, treatment, recovery, complications and any intervention. Results: Most of the patients were from age group 41-55 years. Female patients were more than male patients. Etiology was mostly gall stone, alcohol, idiopathic, post ERCP and trauma. Pain, distention abdomen, vomiting, fever and jaundice were presenting features. Serum amylase, serum lipase, USG abdomen and CECT abdomen were diagnostic investigations. Complications included local and systemic. Mortality was 7%. Conclusions: Acute pancreatitis is mild in most of the cases and recovery is good. Severe cases should be meticulously treated as mortality rates are higher. They should be treated in ICU under the guidance of intensivist. Our study results show that patients with severe diseases should be meticulously monitored clinically, biochemically, haemodynamically and radiologically.